2017
DOI: 10.3390/ijms18020362
|View full text |Cite
|
Sign up to set email alerts
|

Localisation Microscopy of Breast Epithelial ErbB-2 Receptors and Gap Junctions: Trafficking after γ-Irradiation, Neuregulin-1β, and Trastuzumab Application

Abstract: In cancer, vulnerable breast epithelium malignance tendency correlates with number and activation of ErbB receptor tyrosine kinases. In the presented work, we observe ErbB receptors activated by irradiation-induced DNA injury or neuregulin-1sans-serifβ application, or alternatively, attenuated by a therapeutic antibody using high resolution fluorescence localization microscopy. The gap junction turnover coinciding with ErbB receptor activation and co-transport is simultaneously recorded. DNA injury caused by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 156 publications
(196 reference statements)
1
30
0
Order By: Relevance
“…Radiation treatment of cells is known to drive EGFR to the nucleus as part of the DNA-repair pathway mechanism, and studies have shown that treatment of irradiated cells with cetuximab will inhibit EGFR trafficking to the nucleus in both lung carcinoma and breast cancer cell lines [137] . Radiation treatment, along with neuregulin stimulation or trastuzumab will also promote retrograde trafficking of ErbB2-ErbB3 dimers to the nucleus, visible by super-resolution confocal microscopy as demonstrated by Pilarczyk et al [138] . Nuclear import might also be inhibited by targeting the importin-β1 molecule through treatment with small molecule inhibitors such as Karyostatin1A to disrupt importin interactions with the GTPase Ran [139] .…”
Section: Therapeutic Targeting Of Retrotranslocationmentioning
confidence: 92%
“…Radiation treatment of cells is known to drive EGFR to the nucleus as part of the DNA-repair pathway mechanism, and studies have shown that treatment of irradiated cells with cetuximab will inhibit EGFR trafficking to the nucleus in both lung carcinoma and breast cancer cell lines [137] . Radiation treatment, along with neuregulin stimulation or trastuzumab will also promote retrograde trafficking of ErbB2-ErbB3 dimers to the nucleus, visible by super-resolution confocal microscopy as demonstrated by Pilarczyk et al [138] . Nuclear import might also be inhibited by targeting the importin-β1 molecule through treatment with small molecule inhibitors such as Karyostatin1A to disrupt importin interactions with the GTPase Ran [139] .…”
Section: Therapeutic Targeting Of Retrotranslocationmentioning
confidence: 92%
“…In-house software (for detailed descriptions see [40,44,[78][79][80][81]) written in MATLAB was used to calculate signal point localizations from blinking events in raw image stacks. In brief, background signals were excluded, and the two-dimensional intensity profile of each fluorescent signal was subjected to Gaussian fitting through the whole image stack.…”
Section: Smlm Data Analysismentioning
confidence: 99%
“…It was shown that cells with different expression levels of EGF-receptors (e.g., ErbB2 in breast cancer or EGFRvIII in glioblastoma) show a different frequency of clustering, and differ in cluster size and molecular arrangements of the clustering receptor molecules [ 26 , 27 , 46 , 51 ]. Since the cluster formation is directly correlated to functional consequences of inter-receptor communication and signaling pathways [ 52 ], it is of high interest to analyze such clusters with respect to molecular treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The results of localization microscopy measurements ( Figure 4 ) revealed a significant difference in the organization of GFP tags, and consequently, Smurf2. The over-expressed functional Smurf2, formed conformation clusters, as is typical for activated proteins (see for instance [ 52 ]) in a more equally distributed environment of single proteins. The over-expressed non-functional Smurf2-CG showed a much stronger formation of clusters in a random environment, which may be due to vesicle formation.…”
Section: Resultsmentioning
confidence: 99%